EDUCAÇÃO: A TEMÁTICA AMBIENTAL NA ATUAÇÃO TEÓRICO/PRÁTICA DE PROFESSORES DO ENSINO BÁSICO, EM GOIÂNIA GO - CORDEIRO, Joselita Modesto (2008)
This work aims to reflect on the theory / practice performance and the training of teachers in regard to environmental issues. This is a study of teachers from two state colleges located in the city of Goiânia-GO. The study of the developed actions in school, the curriculum and teacher training need analysis and reflection and needs to be reconsidered, taking into account the desires of society, especially in regard to environmental issues. Thus it was a theoretical framework about the nature of visions and new perspectives for the education of the future; the lifting of global discussions around the environmental issue and the consequent educational Brazilian legislation concerning the environment; the study of social representations of the environment of teachers recognizing in them the experience; and finally the empirical research whose data was treated qualitatively and quantitatively. As mode sought the social representation and documentary analysis, as instruments for indirect observation of lessons, investigation of projective documents of colleges and interviews(teachers, educational coordinators and Education Department). It is expected with the outcome of this research, contribute to reflection on teacher training being it, initial or continuing and its theoretical / practice performance in the school with regard to environmental issues